2012
DOI: 10.1002/ppul.22543
|View full text |Cite
|
Sign up to set email alerts
|

Clearance of initial mucoid Pseudomonas aeruginosa in patients with cystic fibrosis

Abstract: Background Accelerated lung function decline in cystic fibrosis (CF) is associated with mucoid Pseudomonas aeruginosa infection. Recent data suggest that mucoid P. aeruginosa may amenable to elimination from the airway. We aim to determine whether the initiation of an aggressive antibiotic eradication regimen upon initial discovery of mucoid P. aeruginosa in the CF airway could be successful in clearing the organism from the CF lung. Methods We performed a retrospective analysis of patients with CF who demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…A portion of this data was previously presented as an abstract at the North American CF Conference in Minneapolis, MN 27…”
Section: Methodsmentioning
confidence: 99%
“…A portion of this data was previously presented as an abstract at the North American CF Conference in Minneapolis, MN 27…”
Section: Methodsmentioning
confidence: 99%
“…In a UKbased study [39], 57.8% of the patients with mucoid Pa cleared this organism for more than 1 year and 32.8% remained Pa free for a median time of 55 months after antibiotic treatment. Recently, Troxler et al [40] observed clearance of mucoid Pa in 73.3% of patients undergoing eradication attempt, compared to only 36.6% of the non-treated patients (p b 0.05).…”
Section: Is Eradication Of Mucoid Pa Strains Possible?mentioning
confidence: 98%
“…In lung transplant patients the use of immunosuppressive drugs with altered host immunity, structural abnormalities and impaired mucociliary activity increase the risk of opportunistic infections and even colonisation. It is possible that transformation to mucoid forms of P. aeruginosa increase their resistance to colistin [9]. Colistin resistance may be a minor reason for the inefficiency of colistin therapy, it was identified in two out of 33 P. aeruginosa colonised patients and two out of four Acromobacter sp.…”
mentioning
confidence: 99%